Observed Teleconnections in Northern Winter: Subseasonal Evolution and Tropical Linkages - Baxter, Stephen Robert (2016)
Teleconnections refer to the climate variability links between non-contiguous geographic regions, and tend to be associated with variability in both space and time of the climate’s semi-permanent circulation features. Teleconnections are well-developed in Northern winter, when they influence subseasonal-to-seasonal climate variability, notably, in surface temperature and precipitation. This work is comprised of four independent studies that improve understanding of tropical-extratropical teleconnections and their surface climate responses, subseasonal teleconnection evolution, and the utility of teleconnections in attribution of extreme climate events. After an introduction to teleconnection analysis as well as the major teleconnection patterns and associated climatic footprints manifest during Northern winter, the lagged impact of the Madden-Julian Oscillation (MJO) on subseasonal climate variability is presented. It is found that monitoring of MJO-related velocity potential anomalies is sufficient to predict MJO impacts. These impacts include, for example, the development of significant positive temperature anomalies over the eastern United States one to three weeks following an anomalous convective dipole with enhanced (suppressed) convection centered over the Indian Ocean (western Pacific). Subseasonal teleconnection evolution is assessed with respect to the Pacific-North America (PNA) pattern and the North Atlantic Oscillation (NAO). This evolution is analyzed both in the presence and absence of MJO-related circulation anomalies. It is found that removal of the MJO results only in small shifts in the centers of action of the NAO and PNA, and that in either case there is a small but significant lag in which the NAO leads a PNA pattern of opposite phase. Barotropic vorticity analysis suggests that this relationship may result in part from excitation of Rossby waves by the NAO in the Asian waveguide. An attempt is made to elegantly differentiate between the MJO extratropical response and patterns of ...